ANALISIS MORFOLOGI DAN LITOLOGI TERHADAP KETEBALAN DAN KUALITAS BAUKSIT LATERIT DI DAERAH TAYAN HILIR, KALIMANTAN BARAT - ‘Afin, Lalita; Meirawaty, Mira (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
The research area is part of the IUP OP PT Aneka Tambang concession, located in Tengkuyung Hamlet, Balai Belungai Village, Tayan Hilir District, Sanggau Regency, West Kalimantan. The research area is part of the Schwaner block, primarily composed of igneous rocks, which led to the formation of lateritic bauxite deposits. This research aims to determine the influence of morphology and lithology on the thickness and quality of lateritic bauxite. The research methodology included geological mapping, geomorphological and geological structure analysis, thickness analysis, and analysis of Al2O3, Fe2O3, and SiO2 content. The geomorphology of the research area is grouped into three units: intrusive undulating hills, intrusive steep hills, and swamp deposits. The stratigraphy of the research area, ordered from oldest to youngest, consists of diorite lithological unit, anorthosite lithological unit, pyroxene diorite unit, and alluvium deposits. The geological structure of the research area is characterized by fractures with an orientation of N105°E/74SW. The research results indicate that the lateritic bauxite deposits exhibit varying thicknesses in undulating hill morphology with a slope of 14°. These thickness variations are controlled by intense geological fractures at one location. Lateritization in the mapping area is moderate-strong. The parent rock controls the quality of bauxite; based on the cut-off grade, diorite, anorthosite, and pyroxene diorite yield high-grade bauxite. The bauxite formed in the research area is classified as ferric bauxite, laterite, and kaolinite types.